2009
DOI: 10.1143/jjap.48.06fh18
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneity of Residual Layer thickness in UV Nanoimprint Lithography

Abstract: A new spectrophotometer system is developed for the study on thermal radiation phenomena of real surfaces. This system can measure spectra of reflection and emission of radiation at 93 wavelength points in the near-ultraviolet to infrared region of λ = 0.30-11 µm on one system simultaneously and repeatedly with a cycle time of 2 s. The system is applied to investigate the transition of spectra of reflection and emission of a metal surface in a high-temperature air-oxidation process. It is demonstrated that int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Hiroshima and Atobe [12] found that resist flows only at the region boundary from regions with low density to that with high density in UV nanoimprint by a stamp with both different pattern densities and feature pitches, which can be complemented by our simulation results. The residual resist would flow across the whole patterned field from the region of low pattern density to that of high density if keeping feature pitch constant.…”
Section: Results Of the Non-uniform Pattern (Quartz Mould)supporting
confidence: 71%
See 1 more Smart Citation
“…Hiroshima and Atobe [12] found that resist flows only at the region boundary from regions with low density to that with high density in UV nanoimprint by a stamp with both different pattern densities and feature pitches, which can be complemented by our simulation results. The residual resist would flow across the whole patterned field from the region of low pattern density to that of high density if keeping feature pitch constant.…”
Section: Results Of the Non-uniform Pattern (Quartz Mould)supporting
confidence: 71%
“…He found that high imprint pressure, a thin initial layer, and high fluidity of resist help to form a thin and uniform residual layer. In addition, Hiroshima and Atobe [12] observed that smooth flowing of the resist after filling can homogenise the residual layer. They also proposed a capacity‐equalised mould to reduce the negative effect of pattern density on imprint quality [13].…”
Section: Introductionmentioning
confidence: 99%
“…Using the obtained nano-scale structure as a mold and nanoimprint technology, we transferred the structure onto UV-curable acrylic polymers [11,12]. The nanoimprinting method is described in Fig.…”
Section: Producing Antifouling Sheets For Stentsmentioning
confidence: 99%
“…Using the obtained nano-porous structure as a mold, we transferred the structure onto UV-curable acrylic polymers using nanoimprint technology [7,8]. Figure 8 shows the nanoimprinting method [9,10].…”
Section: Transfer Experiments To Polymermentioning
confidence: 99%